Pemberdayaan Kader dalam Pemantauan Gizi pada Ibu Hamil dengan Kurang Energi Kronik (KEK) di Puskesmas Kota Managaisaki, Tolitoli - Hasni, Hasni; Saman, Saman; Ra'bung, Alfrida Semuel; Evie, Sova; Suswinarto, Dwi Yogyo; Azwar, Azwar (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Chronic Energy Deficiency (CED) is a nutritional deficiency issue that frequently occurs among pregnant women in Indonesia. The purpose of this Community Service activity was to improve the knowledge and skills of health cadres in monitoring the nutritional status of pregnant women with CED through the measurement of body weight (BW) and mid-upper arm circumference (MUAC), thereby enabling effective monitoring of nutritional intake during pregnancy.This activity was conducted using lecture methods with the aid of media such as PowerPoint presentations and LCD projectors, along with Q&A sessions, discussions, and simulations. It was carried out from March 13 to June 25, 2024. The target participants were maternal health cadres in the working area of the Managaisaki City Public Health Center (Puskesmas), Tolitoli, totaling eight individuals.Post-test results indicated an increase in knowledge from 43% to 86%, and an improvement in skills from 60% to 100%. Furthermore, after three months of monitoring, the number of pregnant women with CED decreased from 16 to 14.It can be concluded that this educational activity successfully improved pregnant women’s nutritional awareness for CED prevention and enhanced the cadres' skills in measuring MUAC and BW. It is recommended that the Managaisaki City Health Center schedule annual training for health cadres who have not yet received any, as an effort to provide updated information or continued coaching for trained cadres, and to reinforce previously delivered training materials.